PENGGUNAAN LEARNING MANAGEMENT SYSTEM (LMS) DI SEKOLAH MENEGAH PERTAMA: A SYSTEMATIC LITERATURE REVIEW - SAPUTRI, KENI APRILIA; BAHARUDIN, BAHARUDIN; ASYHA, AGUS FAISAL; BAHRI, SYAIFUL; HASANAH, IDA FADIRATUL; SHABIRA, QONITA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This systematic literature review investigates the use of Learning Management Systems (LMS) in Indonesian junior high schools. The study analyzes 70 publications indexed in Scopus from 2019-2024, focusing on factors influencing LMS adoption. Results highlight the potential of LMS in enhancing learning but reveal challenges including inadequate infrastructure, teacher digital literacy, and holistic evaluation tools. The review emphasizes the importance of considering individual perceptions, digital literacy levels, and the literature review shows the relevance of ICT adoption barriers across levels of individuals, their comprehension of technology and the barriers that both instructors and learners experience in the use of ICT in the regular lessons. The study concludes by suggesting solutions to optimize LMS utilization and improve educational quality in Indonesia. ABSTRAKTinjauan pustaka sistematis ini mengakaji Learning Management System (LMS) di sekolah menengah pertama di Indonesia. Studi ini menganalisis 70 publikasi dari scopus (2019-2024) untuk mengidentifikasi daktor-faktor yang mempengaruhi adopsi LMS, termasuk infrastruktur teknologi, kesiapan guru, dan alat evaluasi holistik. Penelitian ini menyoroti tantangan seperti infrastruktur yang terbatas, literasi digital guru, dan kurangnya alat evaluasi yang komprehensif, serta menekankan perlunya memahami faktor-faktor yang memengaruhi tingkat adopsi LMS. Diagram PRISMA memandu proses seleksi, menghasilkan empat artikel untuk analisis mendalam. Temuan menunjukkan meskipun artikel menawarkan flesibilitas dan aksebilitas, meningkatkan literasi digital dan menyediakan dukungan komprehenshif sangat penting untuk implementasi dan memaksimalkan dampaknya terhadap kualitas pendidikan.